Polymer assembly: Promising carriers as co-delivery systems for cancer therapy. (July 2016) - Li, Nuannuan; Zhao, Lanxia; Qi, Lisi; Li, Zhonghao; Luan, Yuxia
Abstract: Drug-delivery systems, including liposomes, polymeric micelles, polymersomes, hydrogels and other formulations, have attracted much attention in recent years because they can overcome limitations of chemotherapy such as serious side effects, poor water-solubility of chemotherapeutic drugs, and multidrug resistance (MDR) of cancer cells to chemotherapeutic drugs. MDR is one of the major challenges in chemotherapy and causes most of the treatment failures in cancer patients. Until now, delivery systems loading single drugs have not been able to meet clinical demands. Therefore, co-delivery systems loading two or more therapeutic agents, including drugs, genes and functional agents, have received much attention in recent years. These co-delivery systems can not only reverse MDR, but also produce synergistic effects and serve various other functions with different therapeutic purposes. In this review, we summarize the preparation, characterization and application of different polymer assemblies in co-delivery systems for cancer therapy.